Anthropometric study of the caucasian nose in the city of Curitiba: relevance of population evaluation, - Ballin,Annelyse Cristine (2018)
Abstract Introduction Norms and patterns of nasal esthetics are essential for an adequate preoperative evaluation and surgical programming. The esthetic nasal patterns used are a blend of artistic beauty ideals and tracings in models and celebrities. Because they do not consider population measures, they vary according to the period, and allow a discrepancy between the surgeon's preference and the patient's real desire for rhinoplasty. Not all populations wish to obtain an esthetic result according to these values, but prefer a natural result, that is, one with some of the nasal characteristics of the population to which they belong to. The Brazilian population lacks population studies to evaluate its nose measurements. Objective (1) To evaluate the anthropometric measures of Caucasian noses of people living in the city of Curitiba (state of Paraná), and to compare them to the ideal esthetic pattern of the literature; (2) To compare them between genders. Methods This is a prospective cohort study involving 100 Caucasian volunteers at a tertiary hospital in Southern Brazil. Through the frontal and lateral view photos, intercanthal distance, alar distance, nasal dorsum length, nasofrontal angle, nasolabial angle, and nasal tip projection (Goode's method) were obtained. A statistical analysis was performed to compare the measures obtained between genders and with the ideal patterns. Results Comparing the results obtained with those predicted by the esthetic ideals, the sample presented: similar nasolabial angle (p = 0.07), alar width greater than intercanthal distance (p < 0.001), higher nasal tip projection (p < 0.001), larger width-length ratio (p < 0.001), and more obtuse nasofrontal angle (p < 0.001). The nasofrontal angle (p = 0.0008) and the tip projection (p = 0.032) were statistically different between the genders. Men had a smaller nasofrontal angle, and a larger Goode's ratio. Conclusion Except for the nasolabial angle, the measures obtained in the population sample differed from the published esthetic ideals. Comparing the genders, men had a sharper nasofrontal angle, and higher tip projection than women.